DEPPRESION AND ANXIENTY COMMON MENTAL HEALTH DISORDERS IN PUPILS - Sabani, Havva (International Scientific Journal Vision, 2024)
Human life, its phases, difficulties, obstacles, and solutions that can prevent or eliminate these obstacles and facilitate them have always been the subject of psychology and psychiatry. Many factors in life can lead to depression, anxiety, and stress. Depression and anxiety are two of the most common mental disorders. Many individuals with anxiety also experience depression, and vice versa. The dynamics of modern life are increasingly complicating our mental, emotional, and social well-being. In recent years, levels of depression and anxiety, which negatively affect societal peace, have been on the rise. This situation is particularly critical for university students, who are dynamic members of society. Anxiety and depression are more prevalent among university students than the general population. The purpose of this study was to explore the relationship between depression and anxiety among university students